Spiraling Shame and Honor Restored? The Marcan Passion and Resurrection - Hoelke Simpson, April (2025)
In this article, I use a New-Historicist literary approach focused on Roman honor to argue that, when read in narrative time, Mark 14-15 portrays Jesus as first losing honor and then experiencing vindication only after an acutely shameful demise. Such a portrayal of Jesus allows the Gospel to participate in the cultural task of defining honor. Ultimately, the Gospel portrays Jesus as honorable in much the same way that groups such as the Stoics defined honor: related to virtue and status but not dependent on fame. Rather than promoting an overwhelmingly suffering Jesus or a glorified Jesus, Mark makes Jesus's honor and experience of public shame central to his characterization in the Gospel.
Keywords: Gospel of Mark; Honor; Passion; Shame